Crude Oil and Dispersant Cause Acute Clinicopathological Abnormalities in Hatchling Loggerhead Sea Turtles (Caretta caretta) - Harms, Craig A.; McClellan-Green, Patricia; Godfrey, Matthew H.; Christiansen, Emily F.; Broadhurst, Heather J.; Godard-Codding, Céline A. J. (Frontiers in Veterinary Science, 2019)
Following the explosion of the Deepwater Horizon MC252 oil rig in 2010, 319 live sea turtles exposed to crude oil and oil-dispersant (Corexit) combinations were admitted to rehabilitation centers for decontamination and treatment. Treatment of oiled sea turtles was guided by expected physiological and pathological effects of crude oil exposure extrapolated from studies in other species and from a single loggerhead sea turtle (Caretta caretta) study. While invaluable starting points, inherent limitations to extrapolation, and small sample size of the experimental exposure study, reduce their utility for clinical guidance and for assessing oil spill impacts. Effects of dispersants were not included in the previous experimental exposure study, and cannot be effectively isolated in the analysis of field data from actual spills. A terminal study of pivotal temperature of sex determination using eggs salvaged from doomed loggerhead nests provided an opportunity for an ancillary exposure study to investigate the acute effects of crude oil, dispersant, and a crude oil/dispersant combination in sea turtle hatchlings. Eggs were incubated at 27.2–30.8°C, and hatchlings were randomly assigned to control, oil, dispersant, and combined oil/dispersant exposures for 1 or 4 days. Contaminant exposures were started after a 3 day post-hatching period simulating nest emergence. Turtles were placed in individual glass bowls containing aged seawater and exposed to oil (Gulf Coast—Mixed Crude Oil Sweet, CAS #8002-05-9, 0.833 mL/L) and/or dispersant (Corexit 9500A, 0.083 mL/L), replicating concentrations encountered during oil spills and subsequent response. Statistically significant differences between treatments and non-exposed controls were detected for PCV, AST, uric acid, glucose, calcium, phosphorus, total protein, albumin, globulin, potassium, and sodium. The principal dyscrasias reflected acute osmolar, electrolyte and hydration challenges that were more numerous and greater in combined oil/dispersant exposures at 4 days. Clinicopathological findings were supported by a failure to gain weight (associated with normal hatchling hydration in seawater) in dispersant and combination exposed hatchlings. These findings can help guide clinical response for sea turtles exposed to crude oil and crude oil/dispersant combinations, and indicate potential impacts on wildlife to consider when deploying dispersants in an oil spill response.